스케일링 건강보험 급여화 시행 1년 후 치과의료소비자의 인식도 및 만족도조사 - 이보근; Bo Geun Lee; 이정화; Jung Hwa Lee (Han'guk Ch'iwisaeng Hakhoe chi, 2016)
Objectives: The purpose of the study was to examine the recognition and satisfaction of dental care customers after 1 year national health insurance coverage of dental scaling. Methods: A self-reported questionnaire was completed by 477 dental care customers in Gyeongbuk, Busan, Yangsan, and Gyeonggido from July 18 to September 30, 2014 after receiving informed consents. The questionnaire consisted of general characteristics of the subjects(5 items), subjective awareness of oral health(4 items), recognition of scaling(5 items), and recognition and satisfaction of scaling health insurance(5 items). Data were analyzed using SPSS version 20.0 program. Results: Those who recognized the national health insurance coverage of dental scaling accounted for 80.1 percent and 47.2 percent of them got the health insurance coverage via media advertisements. Those who received the scaling service by health insurance coverage accounted for 73.8% and 66.2% of them were very satisfied with the service. Among the customers, 91.8% were satisfied with scaling health allotment. There was a statistical significance between scaling health insurance and subjective oral condition recognition(p<0.01). Through the health insurance coverage scaling service, the oral health in Korea will improve much. Conclusions: The expansion of health insurance coverage of scaling service will provide the universal oral health care for all people. Owing to low cost service, people will actively try to come in contact with public health service in the future.